MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS V MELALUI PENDEKATAN SAINTIFIK DI SDN 13 TRANS RANGKANG - Canda Babasa, Dwi; Kusnanto (STKIP Subang, 2026)
This study aimed to improve students’ learning outcomes in Science and Social Studies (IPAS) through the implementation of a scientific approach in Grade V of SDN 13 Trans Rangkang. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which consisted of two cycles: planning, action, observation, and reflection. The subjects of this study were 27 fifth-grade students. Data collection techniques included observation, tests, and documentation. The results showed that the implementation of the scientific approach improved students’ learning outcomes in IPAS learning. In the pre-cycle stage, the average score of students was 38.88, with only 1 student (3.7%) achieving the minimum mastery criteria. In Cycle I, the average score increased to 55.37 with 10 students (37%) achieving mastery learning. Furthermore, in Cycle II, students’ learning outcomes increased significantly, where most students achieved the minimum mastery criteria. The scientific approach encouraged students to be more active in observing, questioning, experimenting, reasoning, and communicating during the learning process. Therefore, the scientific approach was effective in improving students’ learning outcomes in IPAS subjects for Grade V students at SDN 13 Trans Rangkang.